Developing the quantum-dot single-photon sources with excellent performance by coupling asymmetric microcavity - Xiang You; Yu-Ming He (Physical Review Research)
Semiconductor quantum dots (QDs) coupled with optical microcavities provide an excellent platform for generating high-performance single-photon sources. However, the current microcavity structures are difficult to solve the tradeoff between single-photon purity and indistinguishability without additional filtering, due to challenges in suppressing broad phonon sideband spectrum and two-photon emission in the practical experiments. To address these issues, we have developed a novel asymmetric microcavity that supports two nondegenerate polarized modes, both resonant with a single quantum dot. One cavity mode is broadband and is used for excitation to reduce two-photon emission intensity, while the other is narrowband and is used for collection to enhance the indistinguishability of single-photon sources. This asymmetric microcavity also has the ability to overcome at least half of the photon efficiency loss under polarization filtering. Moreover, our model has employed an excitation pulse that resonates with cavity modes eliminating spectral distortion of intracavity fields, and efficiently achieving deterministic population inversion of QDs compared to an elliptical cavity. Our scheme paves the way to develop the excellent performance single-photon sources with higher brightness, near-unity purity, and indistinguishability without any additional filtering in practical experiments.